2020
DOI: 10.2196/19459
|View full text |Cite
|
Sign up to set email alerts
|

African American Adolescents and Young Adults, New Media, and Sexual Health: Scoping Review

Abstract: Background Rates of sexually transmitted infections and unintended pregnancies are disproportionately high among African American adolescents and young adults (AYA). New media platforms such as social networking sites, microblogs, online video sites, and mobile phone applications may be a promising approach in promoting safe sex and preventing sexually transmitted infections. Objective The purpose of this scoping review was to address promising approach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Additionally, while most participants had phones, some had limited storage or shared the phone with other family members, making them less inclined to download or keep an app, particularly one that stored sensitive information. By contrast, other studies have found that youth appreciate the anonymity available through technology-based sexual health interventions [ 34 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Additionally, while most participants had phones, some had limited storage or shared the phone with other family members, making them less inclined to download or keep an app, particularly one that stored sensitive information. By contrast, other studies have found that youth appreciate the anonymity available through technology-based sexual health interventions [ 34 ].…”
Section: Discussionmentioning
confidence: 83%
“…While ITK was designed for youth in underserved settings including foster care and shelters, health educators were more likely to encounter technology issues such as lack of Wi-Fi and other hardware in non–school settings. This made the implementation of the technology components of the program more challenging [ 34 ]. Additionally, while most participants had phones, some had limited storage or shared the phone with other family members, making them less inclined to download or keep an app, particularly one that stored sensitive information.…”
Section: Discussionmentioning
confidence: 99%
“…However, effects were stronger when assessed with short-term (1–5 months) compared to longer-term (greater than 6 months) follow-ups Condom use & abstinence : There was a small but significant protective effect of technology-based interventions on condom use (d = .23, 95% CI [0.12, 0.34]) and abstinence (d = .21, 95% CI [0.02, 0.40], p = .027) Other SRH outcomes : Compared to control programs, technology-based interventions were also more effective in increasing sexual health knowledge (d = .40, p < .001) and safer sex norms (d = .15, p = .022) and safe sex attitudes (d = .12, p = .016). No impact on safer sex intentions or perceived self-efficacy to engage in safer sexual behavior Teadt et al (2020) [ 23 ] Aim: Scoping review for the use of New media platform for sexual health Methods • 16 studies were included (5 systematic review articles for social media, internet, web/based, social media TXs that included > 130 articles with African American youth) • P: African American AYAs • Types of SRH TXs : utilizing new media for improving contraception or condom use, communicating credible information regarding HIV and STIs, reducing the transmission of HIV and STIs, improving attitudes around sexual health, and promoting STI testing–related behaviors • New media platforms are defined as social networking sites, collaborative websites, blogs (for opinion sharing/discussion), content communities (for entertainment, info sharing), virtual reality/online gaming, communication/messengers. The most common forms utilized within the included studies were social media (e.g., Facebook, Twitter) (k = 10), internet-based interventions (e.g., It’s Your Game- Tech, Keep It Up! )…”
Section: Resultsmentioning
confidence: 99%
“…United Nations Family Planning Association (UNFPA) suggests covering 9 topic areas in SRH services (described above) [ 2 ]. From our review, we found the digital approach of SRH interventions in AYAs were mainly focused on contraception, pregnancy prevention, abstinence promotion [ 23 , 54 , 56 58 ], sexual health promotion (on topics related to STIs, HIV/AIDS, safe sex, risky sex behaviors) [ 23 , 53 , 55 58 ], substance use [ 53 ], family planning counseling, abortion care [ 56 ], and GBV [ 56 ]. The existing AYA e-SRH interventions cover 5 of the 9 SRH areas suggested by the UNFPA, but predominately focus on pregnancy prevention, uptake of contraception, STIs and HIV/AIDS prevention, and treatment referral and follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous CHI interventions exist to prevent HIV [9][10][11][12][13][14][15] and STIs [16,17] among African American youth. Additionally, digital CHI interventions targeting African American populations can be effective at promoting safer sex behaviors [18,19] and can increase access to sexual health information [20,21]. However, few identify factors driving uptake and engagement [22].…”
Section: Introductionmentioning
confidence: 99%